Analysing the role of ultraviolet A1 phototherapy in the treatment of primary cutaneous lichen amyloidosis in a patient with skin phototype 1 - Sam Hughes; Rossel Ahmad; Maryam Kakar; Novakovic Ljubomir; John Ferguson (Clinical Medicine, 2025)
Introduction: Lichen amyloidosis (LA) is a chronic pruritic dermatosis characterised by hyperkeratotic papules, predominantly affecting middle-aged individuals with skin phototypes 4 and 5.1,2 Genetic predispositions include OSMR mutations in Brazilian and Chinese populations and IL-31RA mutations in Taiwanese families.3,4 The condition is notoriously difficult to treat, often resulting in persistent pruritus, excoriation and hyperpigmentation.Despite its established epidemiology, there is little literature on LA in individuals with skin phototype 1. Here, we report a case of LA in a 72-year-old British man with Fitzpatrick skin type 1, highlighting an atypical distribution and sustained resolution of pruritus following UVA1 phototherapy. Materials and Methods: A 72-year-old British man with Fitzpatrick skin type 1 presented with a 2-year history of severely pruritic papules involving the calves, buttocks and intergluteal fold. His medical history included well-controlled hypertension, hypercholesterolaemia and HIV, managed with dolutegravir and lamivudine. His viral load had remained undetectable for over 10 years.Routine bacterial, viral and fungal cultures were negative, serum inflammatory markers were normal and monoclonal gammopathy screening was unremarkable. Histological examination of a 4-mm punch biopsy revealed eosinophilic, amorphous amyloid deposits in the papillary dermis, confirmed with Congo-Red staining and cytokeratin 5 immunohistochemistry. A diagnosis of LA was established.The patient initially underwent a 2-month course of daily topical clobetasol propionate, which failed to alleviate pruritus. He then completed 39 sessions of narrowband ultraviolet B (NB UVB) phototherapy (cumulative dose: 115.07 J/cm2) with no improvement. Given the refractory nature of his symptoms, he started UVA1 phototherapy. Results and Discussion: The patient underwent 40 UVA1 phototherapy sessions (cumulative dose: 9066.8 J/cm2). Marked pruritus reduction was noted by the 20th session, with complete resolution by the 35th session. At his 18-month follow-up, he reported sustained relief, with no recurrence of lesions (Fig 1). The only residual finding was asymptomatic post-inflammatory hyperpigmentation.LA is rarely documented in individuals with skin phototype 1, and treatment outcomes in this group remain unclear. A retrospective study by Guillet et al. analysing 37 White patients with cutaneous amyloidosis identified UVA1 phototherapy with topical corticosteroids as the most effective therapy.5 However, the study included no skin phototype 1 patients, and only one received UVA1 as monotherapy.This case also demonstrated three unique features. First, our patient presented at 72 years of age, significantly later than the reported average.5 Second, his disease involved the buttocks, an uncommon site, although anosacral amyloidosis has been reported in Asian populations.6 Third, while atopy and thyroid dysfunction are known associations with LA,7 its link to HIV is rarely described.8NB UVB is commonly used for pruritic conditions by targeting cutaneous sensory nerve fibres.5 However, given the prominent lichenification in LA, longer-wavelength UVA1 phototherapy may better penetrate the thickened epidermis.9 Conclusion: This case highlights LA in a patient with skin phototype 1, with an atypical distribution and late-onset presentation. The successful resolution of refractory pruritus with UVA1 phototherapy suggests it as an effective treatment for widespread, treatment-resistant LA. Further studies are needed to assess its efficacy in this patient group.